COGNITIVE FUNCTION AND LEVEL OF INDEPENDENCE IN DOING ACTIVITIES OF DAILY LIVING IN THE ELDERLY - Kadek Agung Ayu Laksmi Dewi; Sayu Aryantari Putri Thanaya; I Dewa Ayu Inten Dwi Primayanti; Made Hendra Satria Nugraha (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
The elderly experience structural changes in the function of biological systems in their bodies due to the ageing process they experience. One of the changes that arise in the health aspect as a result of the ageing process is a decline in cognitive function. The decline in cognitive function in the elderly occurs due to gradual changes in the elderly brain, where this can cause the elderly to experience independence in carrying out daily activities. The purpose of this study was to determine the relationship between cognitive function and the level of independence in doing activities of daily living in the elderly in Banjar Ketapian Kelod, Denpasar City. This type of study is an analytic observational study with a cross-sectional design that uses a consecutive sampling technique. The number of subjects obtained in this study was 62 elderly subjects who met the predetermined inclusion and exclusion criteria. Data were collected through interviews using the MoCA-Ina questionnaire to measure cognitive function and interviews using the Barthel index questionnaire to measure daily activities. Spearman rho non-parametric analysis test results from cognitive function with daily activities obtained p value = 0.000 (p <0.05) and correlation coefficient r = 0.648. Based on the results of the study, it can be concluded that the two variables have a strong, meaningful, and directly proportional relationship between cognitive function and the level of independence in doing activities of daily living in the elderly in Banjar Ketapian Kelod, Denpasar City. Keywords: cognitive function; elderly; independence; activities of daily living